Komiks salamin ng pusong Pinoy - Aguilar, Mila D.; Selvido, Ma. Ernie; Institute for Filipino Cinema ([Quezon City] The Institute, 1989)
Shows why comics remain a popular reading form among Filipinos, as explained by comics writers, a sociologist, a psychologist and the ordinary people on the street.
VHS
Host, Ma. Ernie Selvido; editor, Mel L. Bacani III.
Pinoy Tok
Keywords: Comic books, strips, etc. -- Philippines; Journalism; Mass communication